The Correlation of Age with Uric Acid in Kadipiro, Surakarta - Yeti Nurhayati; Tresia Umarianti (Masters Program in Public Health, 2019)
Background: Uric acid is the final product of purine metabolism. Purines (adenine and guanine) are nucleic acid contituents. Purine rotation occurs continuously in the body along with the synthesis and decomposition of DNA and RNA, although there is no intake of purine, a substantial amount of uric acid will still be formed. Uric acid is synthesized mainly in the liver by the xanthine oxidase enzyme. This study aimed to examine the correlation of age with uric acid.Subjects and method: This was a cross-sectional study conducted in Gambirsari Health Center, Kadipiro Village, Mojosongo, Surakarta, Central Java. A sample of 50 gout patients was selected by purposive sampling. The dependent variable was uric acid. The independent variable was age. The data were analyzed by Pearson correlation.Results: There was a correlation between age and uric acid (r= 0.37; p= 0.009).Conclusion: There is a correlation between age and uric acid.Keywords: gout, age, uric acidCorrespondence: